The Implementation of Merdeka Curriculum at SMA PGRI 2 Palembang - Rosani, Meilia; Misdalina, Misdalina; Widayatsih, Tri (Yayasan Sembilan Pemuda Indonesia, 2024)
The implementation of the Independent Curriculum (IKM) requires students to get a good learning experience. For this reason, schools need careful planning, adequate teacher training, and effective management in implementing the curriculum. The purpose of this research is to find out how to plan, implement, and supervise SMA PGRI 2 Palembang in IKM? A qualitative approach is used in research with the case study method. Data collection techniques are carried out through observation, interviews, and documentation. Then use triangulation to test the validity of the data. The results showed that the planning of the Independent Curriculum started with the holding of the Independent Curriculum training which was attended by the Principal, the Learning Committee to be formed and the teachers. Furthermore, developing a curriculum in accordance with the vision and mission by taking into account the needs of students and the school environment. IKM runs in accordance with applicable regulations, but encounters obstacles, including some students who consider the Pancasila Student Profile Strengthening Project (P5) unimportant. Supervision is carried out by the Supervisors of SMA PGRI 2 Palembang, which consist of subject supervisors and school supervisors. Supervisors provide oversight in the preparation of teaching modules, supervision, and oversight in the implementation of P5.